Oral malignant melanoma and pregnancy: a case report - AYAT, Adel (International Arab Journal of Dentistry (IAJD), 2016)
Malignant melanoma of oral mucosa is a rare and fatal tumor that occurs exceptionally during pregnancy. Among one of the theories, several authors have discussed the possibility of mali- gnant transformation of a pigmented lesion of the oral mucosa to malignant melanoma during pregnancy.We report the case of a 30-years-old patient who consulted for an increasing volume of a pigmented lesion during pregnancy that the dentist has diagnosed as a pregnancy epulis. Clinical examination reveals the presence of bluish-black budding tume- faction. Histological and immune-histochemical examination confirmed the diagnosis of malignant melanoma of the palatal mucosa.